PENGRUH MANAJEMEN PROGRAM TAHFID AL-QUR’AN TERHADAP PEMBENTUKAN KARAKTER RELIGIUS SISWA DI MADRASAH TSANAWIYAH - Ibrahim, Tatang; Dian, Dian; Rahmat, Ipan (Jurnal Isema : Islamic Educational Management, 2023)
Education is a tool for growing society, advancing civilization, and preparing future generations to do much for humanity. The management of the tahfidz al-Qur'an program is expected to assist students in developing religious identity. This study aims to see whether the management of the tahfidz al-Qur'an program influences how state MTs students in Tasikmalaya Regency develop their religious character. This study uses the Ex Post Fecto method with a quantitative approach. Questionnaires or questionnaires are used for information gathering. Data analysis using instrumental analysis (validity and reliability), partial analysis per indicator (variable X reality test and Y variable reality test), classical assumption analysis (linearity and normality), correlation test, coefficient of determination analysis, and simple linear regression. The F and T tests are used to test the hypothesis. The results of this study indicate that the impact of implementing the tahfidz al-Qur'an program on assertive personal development at the State Madrasah Tsanawiyah in Tasikmalaya Regency scores 0.001 <0.05, and it has the implication that the relationship between the implementation of the tahfidz al-Qur'an program and a person who firmly has a relationship or association. After that, the correlation coefficient is calculated to be 0.482. Then the coefficient of determination (R Square) shows a range of 0.232, and it implies that the effect of variable X (management of the tahfidz al-Qur'an program) on variable Y (former of religious character) is 23.2% while 76.8% is influenced by various factors outside inspection